Direct control of high magnetic fields for cold atom experiments based on NV centers - Hesse, Alexander; Köster, Kerim; Steiner, Jakob; Michl, Julia; Vorobyov, Vadim; Dasari, Durga; Wrachtrup, Jörg; Jendrzejewski, Fred (Arxiv, 2020)
In atomic physics experiments, magnetic fields allow to control the interactions between atoms, eg. near Feshbach resonances, or by employing spin changing collisions. The magnetic field control is typically performed indirectly, by stabilizing the current of Helmholtz coils producing the large bias field. Here, we overcome the limitations of such an indirect control through a direct feedback scheme, which is based on nitrogen-vacancy centers acting as a sensor. This allows us to measure and stabilize magnetic fields of 46.6 G down to 1.2 mG RMS noise, with the potential of reaching much higher field strengths. Because the magnetic field is measured directly, we reach minimum shot-to-shot fluctuations of 0.32(4) ppm on a 22 minute time interval, ensuring high reproducibility of experiments. This approach extends the direct magnetic field control to high magnetic fields, which could enable new precise quantum simulations in this regime.